Beyond crystal mushes: evidence for uptake of high-T pyroxene antecrysts from mid- to upper crustal andesites into tephras from the Central Plateau, New Zealand. Issue 2 (3rd July 2021) - Zellmer, Georg F.; Iizuka, Yoshiyuki; Lormand, Charline; Moebis, Anja
ABSTRACT: Pyroxene crystals from recent Central Plateau tephras are used to deduce their formation conditions through two-pyroxene thermobarometry. Crystals return pseudo-pressures and pseudo-temperatures that are artefacts of uptake of antecrysts formed at a range of crustal levels by isobaric cooling of previously intruded magmas. MELTS modelling of tephra glass compositions shows that pseudo-PT conditions are reproduced at oxygen fugacities above the nickel-nickel oxide buffer (NNO+1, NNO+2), mid- to upper crustal pressures (100–400 MPa), and temperatures between c . 900°C and >1100°C. Modelled crystals from the deep crust (800 MPa) are restricted to clinopyroxenes. However, these display chemical equilibrium with shallow orthopyroxenes at higher pseudo-PT conditions than observed in Central Plateau pyroxenes. The data indicate uptake of high-temperature pyroxenes at mid- to shallow crustal levels into ascending andesitic melts and thus preclude the presence of long-lived crustal mush zones (<1000°C) as a source for the crystal cargo of the Central Plateau tephras studied here. Further, the apparent absence of deep crustal pyroxene antecrysts does not preclude models of arc andesite genesis without a 'deep crustal hot zone' beneath the Central Plateau. Generation and ascent of primary andesites from a heterogeneous mantle wedge is therefore a possible scenario at the southern Hikurangi margin.